2011
DOI: 10.1093/aob/mcr138
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from Plectocephalus (Compositae, Cardueae-Centaureinae): ITS disorientation in annuals and Beringian dispersal as revealed by molecular analyses

Abstract: The natural status of the genus Plectocephalus is confirmed and several nomenclatural combinations are proposed. New evidence contributes to the debate concerning problems posed by the use of ITS in the phylogenetic reconstruction of groups that differ in terms of their life cycles. Dispersal from Caucasus and Anatolia along the Siberian route and then across the Bering Land Bridge follows a route previously proposed for other taxonomic groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 59 publications
(73 reference statements)
3
25
0
1
Order By: Relevance
“…The Bayesian consensus tree in Fig. 1 illustrates the phylogenetic distribution of species of the four possible biogeographic and ecological categories used in this study (invasive, noninvasive exotic, native, and not present in CAFP), and is largely congruent with previous studies, including the paraphyly of subtribe Carduinae and strong support for the monophyly of Centaureinae as traditionally circumscribed (80,83). Nonnative (introduced) species were classified as either invasive or noninvasive based on the California Invasive Plant Council invasive plant inventory (84).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The Bayesian consensus tree in Fig. 1 illustrates the phylogenetic distribution of species of the four possible biogeographic and ecological categories used in this study (invasive, noninvasive exotic, native, and not present in CAFP), and is largely congruent with previous studies, including the paraphyly of subtribe Carduinae and strong support for the monophyly of Centaureinae as traditionally circumscribed (80,83). Nonnative (introduced) species were classified as either invasive or noninvasive based on the California Invasive Plant Council invasive plant inventory (84).…”
Section: Resultssupporting
confidence: 83%
“…Sampling was based on previous systematics studies (80,83,101) to represent most of the genera and major clades of the tribe Cardueae. Plant material was collected both from the field and herbarium specimens.…”
Section: Methodsmentioning
confidence: 99%
“…The diversification of this group in the Atacama Desert during the Pliocene, isolated on the western slope of the Andes, was probably facilitated by Andean uplift and the subsequent development of aridity (Sepulchre et al, 2009). This scenario was also suggested for the origin of monotypic Gypothamnium (Asteraceae) in the Atacama Desert ) and for Plectocephalus in South America (Asteraceae; Susanna et al, 2011). On the south-eastern side of the Andes, the onset of diversification of Heliotropium sect.…”
Section: The Andes As Promoters Of Diversification Outside the Andesmentioning
confidence: 72%
“…This group is always placed in a basal position, far removed from the bulk of the genus . A recent survey of Centaureinae and Plectocephalus (Susanna et al, 2011), based on nuclear internal transcribed spacers (ITS) analyses, identified Stizolophus and Zoegea as sisters to the rest of this group.…”
Section: Chemotaxonomic Remarksmentioning
confidence: 99%